Photonic crystal-assisted visible light activated TiO2 photocatalysis - V. Likodimos (Applied Catalysis B: Environmental, 2018)
Photonic crystals have been established as unique periodic structures to promote photon capture and control over light-matter interactions. Their application in semiconductor, mainly TiO2, photocatalysis has emerged as a promising structural modification to boost light harvesting of photocatalytic materials by means of slow photons i.e. light propagation at reduced group velocity near the edges of the photonic band gap (PBG). In this review, the latest advances in the development of TiO2 photonic crystal photocatalysts are highlighted, targeting primarily on the design, fabrication, structure-activity and performance evaluation of visible light activated (VLA) TiO2 inverse opals in the degradation of water and air pollutants as well as water splitting. Up to date work demonstrating the amplification effect of PBG engineered photonic crystals on the photocatalytic and photoelectrochemical performance under UV excitation is accordingly presented. Recent developments on the combination of enhanced light trapping, mainly via slow photons, mass transport and adsorption of macro/mesoporous inverse opals with targeted compositional and electronic modifications currently pursued to promote charge separation and visible light activation, i.e. dye sensitization, non-metal and self-doping, coupling with metallic nanoparticles and plasmonic effects, heterostructuring with narrow band gap semiconductors, quantum dots and graphene as well as the use of alternative metal oxide photocatalysts beyond TiO2 are thoroughly reviewed with respect to their potential for key improvements of the photocatalytic efficiency under visible light. Pertinent challenges and future prospects in photonic crystal-assisted VLA photocatalysts are addressed aimed at advanced photon management routes that could step up photocatalytic applications. © 2018 Elsevier B.V.